2016
DOI: 10.1038/srep34072
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo study of additive manufactured porous Ti6Al4V scaffolds for repairing bone defects

Abstract: Metallic implants with a low effective modulus can provide early load-bearing and reduce stress shielding, which is favorable for increasing in vivo life-span. In this research, porous Ti6Al4V scaffolds with three pore sizes (300~400, 400~500, and 500~700 μm) were manufactured by Electron Beam Melting, with an elastic modulus range of 3.7 to 1.7 GPa. Cytocompatibility in vitro and osseointegration ability in vivo of scaffolds were assessed. hBMSCs numbers increased on all porous scaffolds over time. The group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(129 citation statements)
references
References 40 publications
4
119
0
Order By: Relevance
“…Pore size and porosity have been shown to alter the degree of osseointegration of porous implants in vivo and in vitro cellular response. Studies examining varying pore sizes in AM femoral bone defect implants in goats demonstrated an ability for cells to infiltrate and produce new bone at 300–400 μm, while other studies in rabbits have shown that 600 μm pore size enhances osseointegration compared to 300 and 900 μm (Li et al, ; Taniguchi et al, ). These variabilities in outcomes suggest other factors contribute to the osseointegration of a porous implant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pore size and porosity have been shown to alter the degree of osseointegration of porous implants in vivo and in vitro cellular response. Studies examining varying pore sizes in AM femoral bone defect implants in goats demonstrated an ability for cells to infiltrate and produce new bone at 300–400 μm, while other studies in rabbits have shown that 600 μm pore size enhances osseointegration compared to 300 and 900 μm (Li et al, ; Taniguchi et al, ). These variabilities in outcomes suggest other factors contribute to the osseointegration of a porous implant.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of biomimetic architecture most likely contributes through altered cytoskeletal reorganization that activates signaling pathways which increase osteoblast response. Previous studies have shown that cytoskeletal reorganization in response to implant surface or cell spanning of pores results in increased production of osteoblast markers (Lai et al, ; Li et al, ; Lo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential the applied stress [24] resulting in differences in the internal structure (porosity and composition) and mechanical properties of the bone along its dimensions. For example, the elastic modulus of trabecular bone at the ends of long bones or within the interior of vertebrae is around 0.5 GPa [25]. This variation in elastic modulus depending on the location in the bone indicates the need for development of gradient structures in bone scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…None of the commonly used reconstructive techniques has been able to provide optimal results in case of Paprosky 3A and 3B bone defects [18,19]. In the recent years, several Authors have therefore begun to use custom-made 3D-printed prostheses in non-oncologic settings, with encouraging results [15,[20][21][22]. Some Authors reported encouraging results with custom 3D-printed tri-flanged acetabular implants for the management of severe acetabular defects: Taunton et al retrospectively analyzed 57 patients with pelvic discontinuity reporting a stable implant at a mean follow-up of 65 months, despite high incidence of complications [21].…”
Section: Discussionmentioning
confidence: 99%